Children's active transportation - Larouche, Richard (Elsevier, 2018)
Children's Active Transportation is a rigorous and comprehensive examination of the current research and interventions on active transportation for children and youth. As the travel behaviors of these groups tend to be highly routinized, and their mobility faces unique constraints, such as parental restrictions, mandatory school attendance, and the inability to drive a motor vehicle before late adolescence, this book examines the key factors that influence travel behavior among children and youth, providing key insights into lessons learned from current interventions. Readers will find a resource that clearly demonstrates how critical it is for children to develop strong, active transportation habits that carry into adulthood. Discusses the correlates that exist between children's active transportation using a social and ecological model Summarizes active transportation interventions that show what works to increase non-motorized modes of travel in childrenDescribes the factors that influence the implementation and effectiveness of interventions.